2020
DOI: 10.1155/2020/4237163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wetting-Drying Cycle on the Deformation and Seepage Behaviors of Rock Masses around a Tunnel

Abstract: Water inrush caused by the wetting-drying cycle is a difficult problem in tunnel excavation. To investigate the effect of the wetting-drying cycle on the stability of the tunnel surrounding rock, physical experiments and numerical simulations regarding the process of tunnel excavation with different wetting-drying cycle numbers were performed in this study. The evolutions of stress, displacement, and pore water pressure were analyzed. With the increase in cycle number, the pore water pressure, vertical stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Water-rock interaction is a problem faced in almost all tunneling projects (Guo et al 2020). A large number of studies have shown that in soft rock tunnels, long-term water-rock interactions are an important cause of tunnel damage during construction and operation, with many tunnels suffering from water softening of mudstone (Cui et al 2018).…”
Section: Surrounding Rock Deteriorationmentioning
confidence: 99%
“…Water-rock interaction is a problem faced in almost all tunneling projects (Guo et al 2020). A large number of studies have shown that in soft rock tunnels, long-term water-rock interactions are an important cause of tunnel damage during construction and operation, with many tunnels suffering from water softening of mudstone (Cui et al 2018).…”
Section: Surrounding Rock Deteriorationmentioning
confidence: 99%
“…Zhou et al 25 investigated the process and characteristics of crack initiation, extension and penetration in rocks. Guo et al 26 explored the effects of wet and dry cycles on the stability of rocks around tunnels using numerical simulation. Fu et al 27 investigated the crack extension and mechanical response of marble under three different cyclic loads by numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Water-rock interaction is one of the important factors that cause the geological hazards, and the processes of deformation, destabilization, and damage of rock masses often involve water, such as rainfall leading to slope sliding [1,2], water level rise and fall causing dam base landslides [3,4], water-rich roadway and tunnel roof destabilization [5,6], and groundwater flowinduced earthquakes [7]. Water-rock interaction in coal mining can have a negative impact on engineering rock stability and constitute a severe threat to coal mine safety production.…”
Section: Introductionmentioning
confidence: 99%